2023
DOI: 10.1177/20503121231153511
|View full text |Cite
|
Sign up to set email alerts
|

Preconception care in sub-Saharan Africa: A systematic review and meta-analysis on the prevalence and its correlation with knowledge level among women in the reproductive age group

Abstract: Objective: Preconception care is aimed to promote optimal health in women before conception to reduce or prevent poor pregnancy outcomes. Although there are several published primary studies from sub-Saharan African countries on preconception care, they need to quantify the extent of preconception care utilization, the knowledge level about preconception care, and the association among women in the reproductive age group in this region. This systematic review and meta-analysis aimed to estimate the pooled util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The researchers believe that if WCBA are made aware of PCC, most are likely to utilize it and thus improve their perinatal outcomes. The findings of this study echo those of Woldeyohannes [ 26 ] and Okemo et al [ 27 ], who also found that most WCBA were not aware of PCC and thus likely not to use the service. A study by M’hamdi et al [ 28 ] also concluded that a lack of awareness of PCC is a barrier to its utilization.…”
Section: Discussionsupporting
confidence: 88%
“…The researchers believe that if WCBA are made aware of PCC, most are likely to utilize it and thus improve their perinatal outcomes. The findings of this study echo those of Woldeyohannes [ 26 ] and Okemo et al [ 27 ], who also found that most WCBA were not aware of PCC and thus likely not to use the service. A study by M’hamdi et al [ 28 ] also concluded that a lack of awareness of PCC is a barrier to its utilization.…”
Section: Discussionsupporting
confidence: 88%
“…While prenatal care is offered for free at all primary healthcare clinics, these services are underutilised in both sub-Saharan Africa and SA. [32,33] Transplant recipients should be counselled on factors associated with good pregnancy outcomes. These include delaying pregnancy for at least 1 year following the transplant, no evidence of graft rejection for at least 1 year prior to conception, stable graft function, absence of acute infections, stable maintenance doses of immunosuppressant drugs, and normal blood pressure.…”
Section: Preconception Counsellingmentioning
confidence: 99%
“…Aside from possibly impacting trial outcomes, this finding is concerning for participants' health, as preconception hypertension presents a risk for future cardiovascular disease in mothers [32][33][34], and for adverse outcomes in a potential pregnancy [35][36][37]. The reported undermanagement may reflect a lack of current preconception care within the South African public healthcare system [38][39][40]. In response to this finding, the Bukhali intervention team plans to implement more extensive follow-up of these high-risk, unmanaged cases.…”
Section: Navigating and Bridging The Health Care Systemmentioning
confidence: 99%